Forage value of Elymus breviaristatus (Hitchc.) Á. Löve Subsp. Scabrifolius y E. Scabriglumis (Hack.) Á. Löve (Poaceae) of southeast of Buenos Aires province (Argentine) based on histofoliar characters) - Nuciari, M. C. (Agrociencia Uruguay, 2006)
Hystofoliar charactereres of two forage species of the southeast of Buenos Aires province, Elymus breviaristatus (Hitchc.) Á Löve subsp. scabrifolium and Elymus scabriglumis (Hack.) Á Löve It were analyzed in order to estimated their forage value. The semi laminar area, schlerenchymatic fibers and area and number of vascular bundle, as well as chlorenchyma, parenchyma, schlerenchyma, vascular bundle sheaths, epiderms, phloem and xylem percentages were estimated. These were taken in blades and sheaths and at vegetative and reproductive stages. Seeds of germoplasm banc of EEA (Agropecuary Experimental station) Balcarce of INTA (National Institute of Agropecuary Technology); (E. breviaristatus subsp. scabrifolius BAL 890082, Alo 1384, 13/1/89 (Punta Indio, Buenos Aires province) and E. scabriglumis BAL 890069, Cl 464, 15/3/89, Coronel Dorrego, Buenos Aires province) it were utilized. Germinated seeds were planted in plots in a randomized complete block design with 3 replications. Five cross sections of each of five blades and sheaths were analyzed by plot for each specie and developmental stage. Data were analyzed by Anova with α=0.05 as means comparation. Tissue percentage and hystological character relationships were analyzed by principal components. It was found a specie by leaf part interaction on primary and secundary vascular bundles. The area of the letter differed from specie by developmental stages. In E. breviaristatus subsp. scabrifolius the area of secundary vascular bundle was higher at reproductive stage, while in E. scabriglumis it was on vegetative one. For both species at vegetative stage, means area were higher in sheaths than blades, and were similar in both leaf parts at reproductive stage. The slowly degradable and non degradable tissue percentages in E. breviaristatus subsp.sabrifolius was higher than E. scabriglumis. They were also higher at reproductive stage. If each tissue is considered individually, there were species by leaf part interaction, as well as developmental stage by leaf part and species by developmental stage. The higher percentage of schlerenchyma was observed in sheaths E. breviaristatus subsp. scabrifolius (9.36 vs. 5.5% in E. scabriglumis) and at reproductive stage (9.75 vs. 5.14% at vegeative stage). The principal component analysis indicates a differentiation between leaf parts and developmental sages. Result were discuted related on digestive process and indicated E. breviaristatus subsp. scabrifolius as well as E. scabriglumis, could be consider of potential forage value by their content (lower than 15%) of slowly or non digestible tissue types (TLDI). Neverless, TLDI percentages are 12 % higher at reproductive period, specially in E. breviaristatus subps. scabrifolius, so their forage value decrease more rapidly respect to E. scabriglumis. By the contrair, the constant values in TLDI of E. scabriglumis at developmental stages suggest this specie keep their quality during all the year.